The Mediating Role of Organizational Culture in the Relationship Between Corporate Sustainability and Financial Performance in the Iraqi Banking Sector - Aysar Razak Abd Ali; Ugur Yozgat (European Scientific Journal, ESJ, 2026)
The study aimed to examine how organizational culture mediates the effects of corporate sustainability on financial performance. The study population was managerial employees of Iraqi commercial banks. Data was gathered between March and May of 2025, a period of two months. 2,713 managers and department heads made up the entire population. A random sampling technique was used to guarantee representativeness. The minimum sample size needed for this population was 337 respondents. 337 surveys were sent out in order to accomplish this. Following a thorough review, 328 questionnaires were deemed valid and added to the analysis; the response rate was 97.33%. The study revealed that organizational culture serves as a partial mediator in the relationship between corporate sustainability and financial performance within Iraqi banks. This finding aligns with the broader literature emphasizing the role of internal organizational dynamics in shaping the effectiveness of sustainability initiatives. The study recommended expanding beyond the banking sector to include other industries. Since this research focused solely on Iraqi commercial banks, it would be valuable to investigate whether the observed relationships between corporate sustainability, organizational culture, and financial performance also apply to sectors such as manufacturing, telecommunications, or healthcare.